Association between family function and cigarette addiction in high school students - Nyoman Widhyalestari Parwatha; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani; Wayan Westa; Lely Setyawati; Ni Ketut Sri Diniari (Journal of Clinical and Cultural Psychiatry, 2020)
Background: Cigarette addiction not only affects physical health but also individual mental development. The family function is thought to influence the occurrence of cigarette addiction in adolescents. This study aims to determine the association between family function and cigarette addiction in high school students in Denpasar. Patients and Methods: The study participants were 138 high school students in Denpasar, aged 15-18 years. This study used an analytical cross-sectional method. Measurement of family functions using the Family Assessment Device (FAD) and cigarette addiction measured by the Fagerström Test for Nicotine Dependence (FTND) questionnaire. Data were analyzed descriptively and using the chi-square test with significance level p <0.05. Results: The results showed that high school students who smoked were 29.7%. Most high school students have a good family function (73.2%). There is an association between family function and cigarette addiction in high school students in Denpasar with OR 16.8 (95% CI 6.7-42.1; p <0.001). In this study, the most important dimension from the family function was the problem-solving dimension with OR 8.29 and 95% CI 3.4-20.30 (p <0.001). Conclusion: There is a positive association between family problem and cigarette addiction in high school students in Denpasar.